Low cost optical multi-touch tables: projected versus LCD optical - Más Sansó, Ramón (2013)
Based on our experience, in this paper we present the main aspects of two different approaches to implement low cost multi-touch tables: projection based and LCD based. The former uses a video projector to build a feedback image on the surface of a multi-touch table and the latter uses an LCD display for the same purpose. We discuss the main advantages and disadvantages we have faced during our design and building experiences